Supplemental irrigation: A promising climate-smart practice for dryland agriculture - Nangia, Vinay; Oweis, Theib Y.; Kemeze, Francis H.; Schnetzer, Julian (2018)
Supplemental irrigation - the addition of limited amounts of water to essentially rainfed crops to improve and stabilize yields when rainfall fails to provide sufficient moisture for normal plant growth - is an effective response to alleviating the adverse effects of soil moisture stress on the yield of rainfed crops during dry spells. Supplemental irrigation, especially during critical crop growth stages, can improve crop yield and water productivity.